THE RELATION BETWEEN EARTHQUAKES AND VOLCANOES IN THE SEA EDGE OF THE SOUTH MIDDLE OF VIETNAM IN THE LAST YEARS - Thuc, Pham Van (Vietnam Journal of Marine Science and Technology, 2008)
Eanhquake and volcano are two phenomenons of one geological process. They have a close relation and both are link with deep tectonic faul zones. From June 2005 up to now a series of eaquakes with magnitude from 2.2 to 4.8 have occurred in the shell zone of South of Central Vietnam. They shook many region of which Ho Chi Minh city. The caution is that: these earthquakes occurred at the same area, where group of active volcanoes are locured. At this area Hon Tro volcano group have empled several times, in 1880 - 1882, 1923 and later in 1928, 1978. The 1923 eruplion was most significant. It was well examined by scientists. The results of research show that the heat flow there is high and reaches 335 mw/m2. The area is situated at the tectonic weak zone, which cross cut by fault of Longitude 1090E and NE-SW tectonic faults. This situation makes the zone sensible for eanhquake and volcano. According to scientific judgments the South of Central Vietnam coastal zone could suffer from earthquakes of magnitudes M=5.5 maximum, intensity of VII. In the future the maximum magnitudes and intensity in this region will not be larger than above level, however volcano like Hon Tro in 1923 can take place.